2024
DOI: 10.1097/qai.0000000000003341
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Tenofovir Diphosphate Concentrations in Dried Blood Spots and Virological Outcomes After Initiating Tenofovir–Lamivudine–Dolutegravir as First-Line or Second-Line Antiretroviral Therapy

Jennifer Kate van Heerden,
Graeme Meintjes,
David Barr
et al.

Abstract: Background: Tenofovir diphosphate (TFV-DP) concentration in dried blood spots is a marker of long-term adherence. We investigated the relationship between TFV-DP concentrations and virological outcomes in participants initiating tenofovir–lamivudine–dolutegravir (TLD) as first-line or second-line antiretroviral therapy. Setting: Three primary care clinics in Khayelitsha, Cape Town, South Africa. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Notably, recent in-vivo and in-vitro studies have demonstrated advances and promising results have been noted when TDF-loaded nanoparticles were studied on various cell lines and rat organs for their potential application to manage HIV and associated complications [ 21 23 ]. Although, the current HIV treatment regimen in South Africa containing the preferred first-line ART combination of tenofovir disoproxil fumarate, lamivudine, and dolutegravir (TLD) has produced better treatment outcomes such as viral load suppression, enhanced immune response, and improved clinical indices [ 24 26 ]. Emerging studies have documented several adverse effects including virologic failure and cardio-metabolic disorders secondary to excessive weight gain following initiation and treatement with dolutegravir-based regimen [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent in-vivo and in-vitro studies have demonstrated advances and promising results have been noted when TDF-loaded nanoparticles were studied on various cell lines and rat organs for their potential application to manage HIV and associated complications [ 21 23 ]. Although, the current HIV treatment regimen in South Africa containing the preferred first-line ART combination of tenofovir disoproxil fumarate, lamivudine, and dolutegravir (TLD) has produced better treatment outcomes such as viral load suppression, enhanced immune response, and improved clinical indices [ 24 26 ]. Emerging studies have documented several adverse effects including virologic failure and cardio-metabolic disorders secondary to excessive weight gain following initiation and treatement with dolutegravir-based regimen [ 27 29 ].…”
Section: Introductionmentioning
confidence: 99%